2006
DOI: 10.1080/17453670610013240
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration cytology and core needle biopsy in the preoperative diagnosis of desmoid tumors

Abstract: Background Desmoid tumors have a tendency to recur locally, and traditionally they have been treated surgically. No treatment is sometimes indicated, however; this requires a morphological diagnosis that is not based on a surgical specimen. In this study we aimed to identify the diagnostic accuracy of needle and core biopsy for the morphological diagnosis of desmoid.Methods We compared the diagnostic accuracy of fine-needle aspiration (FNA) and core needle biopsy (CNB) in 69 and 26 patients, respectively, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…Both needle techniques are in most cases easy to perform, cost effective and well tolerated by the patient [2]. In Scandinavia, the further management of the patient is decided upon the pretreatment diagnosis made on tumor cells from FNA and/or tissue from CN biopsies, combined with clinical and radiographic information [3]. Apart from the morphologic evaluation of tumor cells in FNA and CN biopsies, ancillary techniques, such as immunocytochemistry/immunohistochemistry, are often used to improve the diagnostic precision.…”
Section: Introductionmentioning
confidence: 99%
“…Both needle techniques are in most cases easy to perform, cost effective and well tolerated by the patient [2]. In Scandinavia, the further management of the patient is decided upon the pretreatment diagnosis made on tumor cells from FNA and/or tissue from CN biopsies, combined with clinical and radiographic information [3]. Apart from the morphologic evaluation of tumor cells in FNA and CN biopsies, ancillary techniques, such as immunocytochemistry/immunohistochemistry, are often used to improve the diagnostic precision.…”
Section: Introductionmentioning
confidence: 99%
“…Fragments of dense collagenized stroma or matrix can also be seen. 12,13 The FNA biopsy of our case was moderately cellular and displayed variable size tissue fragments with frayed periphery. The fragments were syncytial 3-dimentional and occasional loose clusters or singly dispersed cells were seen.…”
Section: Discussionmentioning
confidence: 94%
“…Table 4 summarizes the advantages of the combined procedure. Therefore, and as shown by other investigators, the utilization of both aspirate smears and core tissue biopsy material are complementary and have added value compared to either one alone [7,13,26,29,33,35,38,39,44,45,46,47,50,51,52,57,58,59,60,61,62,68,75,76,77,78]. …”
Section: Advantages Of the Combined Approachmentioning
confidence: 99%
“…Seven of the sarcoma cases that were diagnosed by FNAB were further subtyped by CNB. In their study that aimed to identify the diagnostic accuracy of FNAB and CNB in diagnosing desmoid tumors, Dalén et al [59] showed that 35 out of 69 (50.7%) cases were diagnosed by FNAB and 24 out of 26 (92.3%) cases were diagnosed by CNB. These findings confirm that CNB is more reliable than FNAB in diagnosing soft tissue lesions, and using the two modalities together would significantly improve the diagnostic accuracy in soft tissue lesions [39,57,59].…”
Section: Advantages Of the Combined Approachmentioning
confidence: 99%